Annual down‐glacier drainage of lakes and water‐filled crevasses at Helheim Glacier, southeast Greenland. Issue 10 (15th October 2016) - Everett, A.; Murray, T.; Selmes, N.; Rutt, I. C.; Luckman, A.; James, T. D.; Clason, C.; O'Leary, M.; Karunarathna, H.; Moloney, V.; Reeve, D. E.
Abstract: Supraglacial lake drainage events are common on the Greenland ice sheet. Observations on the west coast typically show an up‐glacier progression of drainage as the annual melt extent spreads inland. We use a suite of remote sensing and modeling techniques in order to study a series of lakes and water‐filled crevasses within 20 km of the terminus of Helheim Glacier, southeast Greenland. Automatic classification of surface water areas shows a down‐glacier progression of drainage, which occurs in the majority of years between 2007 and 2014. We demonstrate that a linear elastic fracture mechanics model can reliably predict the drainage of the uppermost supraglacial lake in the system but cannot explain the pattern of filling and draining observed in areas of surface water downstream. We propose that the water levels in crevasses downstream of the supraglacial lake can be explained by a transient high‐pressure wave passing through the subglacial system following the lake drainage. We support this hypothesis with analysis of the subglacial hydrological conditions, which can explain both the position and interannual variation in filling order of these crevasses. Similar behavior has been observed in association with jökulhaups, surging glaciers, and Antarctic subglacial lakes but has not previously been observed on major outlets of the Greenland ice sheet. Our results suggest that the behavior of near‐terminus surface water may differ considerably from that of inland supraglacial lakes, with the potential for basal water pressures to influence the presence of surface water in crevasses close to the terminus of tidewater glaciers. Key Points: We observe a down‐glacier order of filling and draining in water‐filled crevasses at Helheim Glacier A model of surface‐melt‐driven hydrofracture cannot satisfactorily explain the observed results We propose a theory which does not rely on hydrofracture in order to explain the results